Does Corruption Lead to Welfare Loss? An Empirical Evidence From Real Estate Sector of Bangladesh - Muzaffar, Ahmed Taneem; Huda, S. S. M. Sadrul (Organizations and Markets in Emerging Economies, 2011)
Regulation may give rise to corrupt practices thereby resulting in welfare loss in an economy. This research aims at measuring the impact of corruption on the real estate sector of Dhaka city, the capital of Bangladesh. It makes an attempt to measure the welfare loss resulting from corrupt practices exercised mainly by government regulatory agencies. Bribe and extortion fee are the two main indicators whereby welfare loss is measured. Evidence from the study reveals that around 8 floors are lost due to payment of bribe and other such payments.
Keywords: Corruption; bribery; extortion fee; rent-seeking activity; real estate sector; welfare loss